The Healing and Pedagogical Significance of Physical Exercises In IBN Sina's Views. (Eurasian Scientific Herald, 2023)
This article reveals the contribution of Abu Ali Ibn Sina to medicine and pedagogy, pedagogical views on a healthy lifestyle in maintaining human health, as well as on the health benefits of physical exercise